Rental price convergence in a developing economy: New evidence from nonlinear panel unit root test - Bilgin, Mehmet Huseyin; Lau, Chi Keung Marco; Demir, Ender; Astrauskienė, Nijolė (International Journal of Strategic Property Management, 2010)
We examine the hypothesis of nonlinear rental price convergence using relative rental price index of three major cities of Turkey namely, Istanbul, Izmir, and Ankara span from the period from January 1994 to February 2010. Our results indicate that all cities exhibit rental price convergence towards its national mean level for the period of January 1994 to December 2004. In contrast, none of the cities show evidence of convergence from January 2005 to February 2010. The evidence clearly shows rental price divergence in Turkish property market. First Published Online: 09 Jun 2011